Ankle Power Generation Has a Greater Influence on Walking Speed Reserve Than Balance Following Traumatic Brain Injury. Issue 2 (28th March 2022) - Gill, Renee; Banky, Megan; Williams, Gavin
Abstract : Objective: Reduced walking speed is common following traumatic brain injury (TBI). Walking speed reserve (WSR) refers to the ability to increase walking speed on demand and is calculated as the difference between self-selected and fast walking speeds. Walking speed reserve is important for adaptive functional mobility in the community. Predictors of WSR following TBI are yet to be determined. The aim of the study was to identify whether static balance or ankle power generation (APG) was a stronger predictor of WSR following TBI. Setting: A major metropolitan rehabilitation hospital. Participants: A total of 92 individuals receiving inpatient physiotherapy for mobility limitations following TBI were recruited. Design: A cross-sectional study. Methods: Walking speed (self-selected and fast), APG, and a summed single-leg stance scores were measured. The ability to increase walking speed on demand by 0.20 m/s or more defined WSR. Correlations, logistic regression, and receiver operating characteristic (ROC) curve analyses were performed to investigate independent relationships between WSR, APG, and static balance. Results: Fifty participants (54.3%) had a WSR of 0.20 m/s or more. The strongest predictor of WSR was APG (odds ratio [OR] = 3.34; 95% CI, 1.50-7.43) when compared with static balance (OR = 1.03; 95% CI, 1.01-1.06). The ROC curve demonstrated that APG could accurately discriminate between individuals with a WSR from those without (AUC [area under the ROC curve] = 0.79; 95% CI, 0.70-0.88). The APG cutoff score identified on the curve that maximized combined sensitivity (92.0%) and specificity (54.8%) was 0.75 W/kg. Conclusion: Following TBI, APG was a stronger predictor of WSR than static balance. Clinicians should consider interventions that preferentially target APG in order to increase WSR for community mobility.